First Report of Haemoproteus sp. in Hill Mynah Blood in Thailand - Archawaranon, Manee (International Journal of Poultry Science, 2005)
Avian haemosporidian, Haemoproteus sp., which was a common avian blood parasite, was examined in 30 Hill Mynahs Gracula religiosa intermedia. Asexual reproduction found in avian host consisted of schizogony in the tissues and gametocytes which were the only stage found in the red blood cells of birds. The mature gametocyte encircled the erythrocyte nucleus to form a halter-shaped appearance. Results showed that there were only three infected birds. Both macrogametocytes and microgametocytes were recognized. However, further studies on taxonomy of both parasite and vector, together with the relationships among host, vector and parasite are necessary. The finding from this study is hoped to urge a serious investigation of haemosporidian parasites in tropical birds.